ADIKSI GAME ONLINE SEBAGAI TANTANGAN PERKEMBANGAN REMAJA: ANALISIS EMPIRIS DAN RESPON PASTORAL KRISTEN - Mulia Wongdi; Juliana Hindradjat (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
Online game addiction has become a significant developmental challenge for adolescents, particularly in Indonesia with its rapidly growing population of digital game users. This study aims to analyze the phenomenon of online game addiction among adolescents by integrating recent empirical findings with a Christian pastoral-theological perspective. Using a literature review approach, this research examines the causes, symptoms, and psychosocial effects of gaming addiction and interprets their implications for character formation and spiritual maturity. Empirical studies indicate that addiction arises from a combination of internal factors—including the need for recognition, emotional escape, and low self-control—and external factors such as ineffective parenting, peer pressure, and reward-based game design. Its impact extends beyond emotional, social, and academic impairment, affecting adolescents’ spirituality through diminished spiritual disciplines and weakened identity formation. Theologically, addiction is understood as a distortion of freedom and relational wholeness, hindering the adolescent’s growth toward maturity in Christ. This study emphasizes the necessity of a holistic pastoral response through relational guidance, family involvement, and the cultivation of spiritual disciplines as essential strategies for recovery and the strengthening of adolescents’ spiritual identity in the digital age.